Literatur Review: Pengaruh Diet Bebas Gluten (Gluten Free) terhadap Perkembangan Anak Penderita Autis - Awaludin, Triyono Saputra; Hanifah Setiowati; Teguh Wibowo (Politeknik Baubau, 2025)
Autism is a neurological developmental disorder that affects communication, social interaction, and behavior in children. One of the therapies used to reduce autism symptoms is the Casein-Free Gluten-Free (CFGF) diet. This therapy aims to address metabolic disorders caused by the